Applying blended learning at Sofia university, department of botany: results and good practices - Stoyneva-Gärtner, Maya; Uzunov, Blagoy; Kremenska, Annelly (Yearbook Telecommunications, 2018)
This paper aims to share the experience gained from teaching botany at the Faculty of Biology of Sofia University, when classroom teaching is combined with permanent access to digital teaching materials and online tests. We compared a set of long-term data (2002-2017) of exam scores of 3888 students in both classical and blended learning compulsory bachelor courses related to teaching of Algae and Fungi. The results obtained clearly show the advantages of blended education for both teachers and students. It is suggested that e-testing is nature-friendly and green due to zero paper consumption. Taking into account all benefits and traits of e-testing and education, we recommend them to all our colleagues for their future work.